2016
DOI: 10.1055/s-0042-115569
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Distension of Ventricular Mural Architecture Validated Histologically

Abstract: ▼Purpose: There are ongoing arguments as to how cardiomyocytes are aggregated together within the ventricular walls. We used pneumatic distension through the coronary arteries to exaggerate the gaps between the aggregated cardiomyocytes, analyzing the pattern revealed using computed tomography, and validating our findings by histology. Methods: We distended 10 porcine hearts, arresting 4 in diastole by infusion of cardioplegic solutions, and 4 in systole by injection of barium chloride. Mural architecture was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The ventricular walls are composed of chains of cardiomyocytes connected together in end-to-end fashion. In combination with the dense endomysium, myocytic branches serve to aggregate the individual cardiomyocytes into units described as lamellae, or sheets [13,[16][17][18][19][20][21][22][23][24][25][26][27]29]. These aggregated units of cardiomyocytes are markedly heterogeneous in dimensions and shape [25][26][27]],…”
Section: Ii1towards Elucidating the Structure Of The Ventricular Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ventricular walls are composed of chains of cardiomyocytes connected together in end-to-end fashion. In combination with the dense endomysium, myocytic branches serve to aggregate the individual cardiomyocytes into units described as lamellae, or sheets [13,[16][17][18][19][20][21][22][23][24][25][26][27]29]. These aggregated units of cardiomyocytes are markedly heterogeneous in dimensions and shape [25][26][27]],…”
Section: Ii1towards Elucidating the Structure Of The Ventricular Wallsmentioning
confidence: 99%
“…So as to further assess the global nature of this variability, we injected compressed air through the coronary arteries of porcine and bovine hearts, thus pneumatically distending the loose perimysial spaces and making the aggregated units and their associated myocytic connecting branches clearly discernible. When imaged using computed tomography, and the short-axis slices (tomograms) viewed sequentially [28,29], a complex structural pattern is observed. Ascending sub-epicardial and descending subendocardial aggregates are connected by a heterogeneously distributed circumferential zone in between.…”
Section: Ii4 Pneumatic Distention Of the Heartmentioning
confidence: 99%
“…During the last 50 years, morphological research unanimously has shown that the parallel alignment of the myocardial fibres based on Frank's understanding must be replaced by associations of sequentially splitted myocytes forming a continuous spatial network of endless chains of myocytes with no origin or insertion (figure 2). [27][28][29][30][31][32][33][34] Less than a hundred chains are bundled and surrounded by connective tissue to form aggregates with muscle fibres of different orientation 35 (figure 3). Smaller fibres of endless chains form the connection between respective aggregates as a strong network between two adjacent entities.…”
Section: Myocardial Morphology and Functional Anatomymentioning
confidence: 99%